Revitalisasi Sistem Among Ki Hadjar Dewantara dalam Paradigma Baru Kurikulum Merdeka - Farizatul Qamariyah; Novy Eurika; Anisa Faradila (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The Among system is a way of educating children based on the independence and freedom of students so that they can grow according to their personal nature. The among system can create an independent spirit, so students can be independent and more courageous in learning according to their wishes. Currently, the among system is starting to be forgotten because Indonesian education is developing in a modern way by applying foreign education. This phenomenon causes learning to be not persuasive and educative, so it is necessary to revitalize the among system through an independent curriculum so that it can bring change and respond to the challenges of the times. This type of research used is qualitative research literature study. The results of the study show that the among system can be reapplied through the independent curriculum, in which this curriculum carries the concept of independent learning with flexible and essential material, student-centered learning, and in accordance with the interests, talents and potential of students. Differentiated learning is one way to revive the among system in education. Learning facilitates the needs of students, so that students can develop their interests, talents and potential independently.